The Role Of Website Quality And Continuous-Use Intention Towards Online Banking Performance Of Jordanian Commercial Banks - Tariq Barjes Salameh Al-Bloush
The importance of continuous-use intention to explain the impact of website quality components on online banking performance has been an issue of concern for many researchers. Therefore, this research examined the impact of information quality, system quality, and e-service quality on continuous-use intention and online banking performance, as well as the influence of continuous-use intention on online banking performance. It also examined the mediating impact of continuous-use intention on the relationship between the independent variables and online banking performance. Data from 372 respondents were analysed using PLS-SEM. The results indicated that online banking performance was significantly influenced by INQ, SYQ, and E-SQ. These present valuable insights for researchers and decision-makers to improve website quality components, considering their critical role in online banking performance success. Further analyses showed that the effects of the independent variables, namely INQ, SYQ, and E-SQ, on continuous-use intention were positive and significant. This study also found that continuous-use intention had a positive and significant effect on online banking performance. Continuous-use intention mediated the negative and positive relationships between the three independent variables and online banking performance. More specifically, the study found that continuous-use intention had a positive mediation effect on the relationship between SYQ, E-SQ, and online banking performance, while it had a negative mediation effect on the relationship between INQ and online banking performance. Therefore, an excessive focus on INQ may result in lower online banking performance due to lower continuous-use intention. The findings suggest the important role of continuous-use intention in increasing the effects of these variables on online banking performance. Therefore, decision-makers need to develop a correct configuration of these components, thus giving Jordanian commercial banks superior economic results over their competitors. In turn, this would lead to a higher level of continuous-use intention and better online banking performance.